THE INFLUENCE OF SERVICE QUALITY,FACILITIES,AND LOCATION ON TOURIST SATISFACTION AT ISTANA MAIMUN TOURISM OBJECT - Thalia Ayu Permatasari; Ade Rahma Ayu (SEAN Institute, 2023)
The purpose of this study was to determine whether there is an influence of service quality,facilities and location on visitor satisfaction at the Maimun Palace tourist attraction in Medan. The sample of this research was 78 visitors at Maimun Palace. The method used in this study is a quantitative method with multipe linear regression analysis techniques. The data used are secondary data and primary data, hypothesis testing uses the coefficient of determination test (R²), Simultaneous Test (F) and Partial Test (t) with calculations using the SPSS 22 program. The results show that the quality of service,facilities and locations can explain its exixtence to the variable visitor satisfaction,besides the partially and simultaneously service quality,facilities and location affect visitor satisfaction.